2020
DOI: 10.3389/fnagi.2020.00269
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Quality of Life According to Cognitive Status in Parkinson’s Disease

Abstract: Background: Quality of life (QoL) was worse in Parkinson's disease patients with mild cognitive impairment (PD-MCI) or dementia (PDD) than PD patients with normal cognition (PD-NC). The aim of this study was to investigate and compare the potential heterogeneous determinants of QoL in PD patients with different cognitive statuses. Methods: We recruited 600 PD patients, including 185 PD-NC patients, 336 PD-MCI patients and 79 PDD patients, in this cross-sectional study. All patients completed the QoL assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
(68 reference statements)
2
19
0
Order By: Relevance
“…The Epworth Sleepiness Scale (ESS) 18 was used to evaluate excessive daytime sleepiness. The Mini Mental State Examination (MMSE) 19 was performed to assess global cognitive function, and a full set of neuropsychological tests for five specific cognitive domains were performed as previously described 20,21 . The routinely used Parkinson's Disease Questionnaire (PDQ‐39) was conducted to determine QoL and included eight subscales 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Epworth Sleepiness Scale (ESS) 18 was used to evaluate excessive daytime sleepiness. The Mini Mental State Examination (MMSE) 19 was performed to assess global cognitive function, and a full set of neuropsychological tests for five specific cognitive domains were performed as previously described 20,21 . The routinely used Parkinson's Disease Questionnaire (PDQ‐39) was conducted to determine QoL and included eight subscales 22 …”
Section: Methodsmentioning
confidence: 99%
“…The Mini Mental State Examination (MMSE) 19 was performed to assess global cognitive function, and a full set of neuropsychological tests for five specific cognitive domains were performed as previously described. 20,21 The routinely used Parkinson's Disease Questionnaire (PDQ-39) was conducted to determine QoL and included eight subscales. 22 Cognitive classifications SCC was diagnosed if there was no evidence of cognitive impairment on standard tests and the patient's answer to the following single question is "yes" as previously recommended: "Over the past week have you had problems remembering things, following conversations, paying attention, thinking clearly, or finding your way around the house or in town?".…”
Section: Clinical and Neuropsychological Assessmentsmentioning
confidence: 99%
“…The performed Spearman's correlation analysis showed the following influence of certain factors on HRQOL: disease duration (R = 0.30, p < 0.001), tremor dominant (R = -0.17, p = 0.006), MMSE (R = -0.25, p = 0.0001), cognitive impairment (R = 0.38, p < 0.0001), depressed mood (R = 0.35, p < 0.0001), anxious mood (R = 0.29, p < 0.0001), apathy (R = 0.33, p < 0.0001), night-time sleep problems (R = 0.29, p < 0.0001), daytime sleepiness (R = 0.35, p < 0.0001), pain and other sensations (R = 0.38, p < 0.0001), urinary problems (R = 0.30, p < 0.0001), constipation problems (R = 0.13, p = 0.0281). In addition, Fan et al [15] also assessed the determinants of quality of life in patients with PD. It was shown that the most severe determinant of the QOL was The Epworth Sleepiness Scale (R² = 0.02, β = 0.44, p = 0.0099), GDS score (R² = 0.35, β = 1.05, p < 0.0001), female (R² = 0.01, β = 3.38, p = 0.0257) and disease duration (R² = 0.04, β = 0.83, p = 0.0116).…”
Section: Quality Of Life In Parkinson's Diseasementioning
confidence: 99%
“…Among the motor symptoms, resting tremor, rigidity, postural instability, slowness of movement, and freezing while walking are particularly disabling [ 2 ] and, because pharmacological treatments cannot fully compensate or relieve them, greater issues arise. Recurrent falls (~39%, ~20 falls per year) [ 3 ]; frequent rehospitalizations to acute care (patients with a history of hospitalization are 1.7 times more likely to undergo re-hospitalization compared to those without a prior event) [ 4 ]; and admission to long-term care facilities (5–10% prevalence of PD among all patients) [ 5 ], depression, and cognitive impairment, among others, have been reported to significantly impact the quality of life of patients with PD [ 6 ] and, ultimately, to increase their likelihood of developing other comorbidities and dying prematurely [ 7 ].…”
Section: Introductionmentioning
confidence: 99%